A Pharmacokinetic and Pharmacodynamic Evaluation of the Anti-Hepatocellular Carcinoma Compound 4-N-Carbobenzoxy-gemcitabine (Cbz-dFdC) - Yilin Sun; Jiankun Wang; Kun Hao (Molecules, 2020)
Gemcitabine (dFdC) demonstrates significant effectiveness against solid tumors in vitro and in vivo; however, its clinical application is limited because it tends to easily undergo deamination metabolism. Therefore, we synthesized 4-N-carbobenzoxy-gemcitabine (Cbz-dFdC) as a lead prodrug and conducted a detailed pharmacokinetic, metabolic, and pharmacodynamic evaluation. After intragastric Cbz-dFdC administration, the Cmax of Cbz-dFdC and dFdC was 451.1 ± 106.7 and 1656.3 ± 431.5 ng/mL, respectively. The Tmax of Cbz-dFdC and dFdC was 2 and 4 h, respectively. After intragastric administration of Cbz-dFdC, this compound was mainly distributed in the intestine due to low carboxylesterase-1 (CES1) activity. Cbz-dFdC is activated by CES1 in both humans and rats. The enzyme kinetic curves were well fitted by the Michaelis–Menten equation in rats’ blood, plasma, and tissue homogenates and S9 of the liver and kidney, as well as human liver S9 and CES1 recombinase. The pharmacodynamic results showed that the Cbz-dFdC have a good antitumor effect in the HepG2 cell and in tumor-bearing mice, respectively. In general, Cbz-dFdC has good pharmaceutical characteristics and is therefore a good candidate for a potential prodrug.